Correlation and underlying brain mechanisms between rapid eye movement sleep behavior disorder and executive functions in Parkinson’s disease: an fNIRS study - Ren, Lu; Yin, Xiaoxue; Wang, Hai-Yang; Hao, Xinqing; Wang, Da; Jin, Feng; Zhang, Tingting; Li, Tao; Zhou, Tingting; Liang, Zhanhua (Frontiers in Aging Neuroscience, 2024)
Purpose: Rapid eye movement sleep behavior disorder (RBD) affects 30-40% of patients with Parkinson's disease (PD) and has been linked to a higher risk of cognitive impairment, especially executive dysfunction. The aim of this study was to investigate the brain activation patterns in PD patients with RBD (PD-RBD+) compared to those without RBD (PD-RBD-) and healthy controls (HC), and to analyze the correlation between changes in cerebral cortex activity and the severity of RBD.We recruited 50 PD patients, including 30 PD-RBD+, 20 PD-RBD-, and 20 HCs.We used functional near infrared spectroscopy during a verbal fluency task (VFT-fNIRS) and clinical neuropsychological assessment to explore the correlation between PD-RBD+ and executive function and changes in neural activity.The VFT-fNIRS analysis revealed a significant reduction in activation among PD-RBD+ patients across multiple channels when compared to both the PD-RBD-and HC groups. Specifically, PD-RBD+ patients exhibited diminished activation in the bilateral dorsolateral prefrontal cortex (DLPFC) and the right ventrolateral prefrontal cortex (VLPFC) relative to their PD-RBD-counterparts. Furthermore, compared to the HC group, PD-RBD+ patients displayed reduced activation specifically in the right DLPFC.Significantly, a noteworthy negative correlation was identified between the average change in oxygenated hemoglobin concentration (ΔHbO2) in the right DLPFC of PD-RBD+ patients and the severity of their RBD.Our study offers compelling evidence that RBD exacerbates cognitive impairment in PD, manifested as executive dysfunction, primarily attributed to reduced prefrontal activation. These aberrations in brain activation may potentially correlate with the severity of RBD.